Cover Feature: Green‐, Red‐, and Infrared‐Emitting Polymorphs of Sterically Hindered Push–Pull Substituted Stilbenes (Chem. Eur. J. 13/2021). Issue 13 (7th January 2021) - Pauk, Karel; Luňák, Stanislav; Růžička, Aleš; Marková, Aneta; Mausová, Anna; Kratochvíl, Matouš; Melánová, Klára; Weiter, Martin; Imramovský, Aleš; Vala, Martin
Abstract : Recrystallization of the first polymorph gave rise to a second polymorph, accompanied by a dramatic increase of fluorescence intensity from moderate (5%) red monomer‐type to intense (32%) infrared excimer‐type. More information can be found in the Full Paper by M. Vala et al. on page 4341 .